2021
DOI: 10.1080/09638288.2021.1924298
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of physical activity levels in children and adolescents after surgery for congenital heart disease: preferences and use of physical therapy

Abstract: Purpose: After surgery for congenital heart disease in children and adolescents, an active lifestyle is important to achieve and maintain good physical fitness. This study aimed to describe physical activity, as well as the use of patients' and parents' preferences for rehabilitative care after surgery for congenital heart disease. Methods: This cross-sectional study included patients aged 4-16 years old, who had undergone surgery for congenital heart disease 2 years prior to the study onset. Patients and/or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The traditional treatment of VSD is open thoracotomy under CPB. However, this technique requires median sternal incision, great trauma, more bleeding during operation, slow recovery after operation, CPB and transfusion of blood products, and potential complications of CPB after operation, such as cognitive dysfunction, coagulation disorder, and renal dysfunction [ 18 ]. The healing deformity after sternotomy and the incision scar located in the middle of the chest can cause psychological disorders and affect the long-term quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The traditional treatment of VSD is open thoracotomy under CPB. However, this technique requires median sternal incision, great trauma, more bleeding during operation, slow recovery after operation, CPB and transfusion of blood products, and potential complications of CPB after operation, such as cognitive dysfunction, coagulation disorder, and renal dysfunction [ 18 ]. The healing deformity after sternotomy and the incision scar located in the middle of the chest can cause psychological disorders and affect the long-term quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The healing deformity after sternotomy and the incision scar located in the middle of the chest can cause psychological disorders and affect the long-term quality of life of the patients. Percutaneous interventional occlusion of VSD in internal medicine was first completed by van Egmond Dam et al in the 1970s [ 18 ]. Due to its minimally invasive and beautiful incision, it is widely accepted [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that the majority of a CHD cohort did not meet guidelines for physical fitness and had not received physical therapy 2 years post-operatively. Further investigation should be conducted to determine if participation in physical therapy by patients with CHD will promote motor skill development [ 135 ].…”
Section: Post-operative Neuroprotection—clinical Studiesmentioning
confidence: 99%